2017
DOI: 10.1016/j.foodchem.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 and CYP2A6 biotransform dietary tyrosol into hydroxytyrosol

Abstract: The dietary phenol tyrosol has been reported to be endogenously transformed into hydroxytyrosol, a potent antioxidant with multiple health benefits. In this work, we evaluated whether tyrosine hydroxylase (TH) and cytochrome P450s (CYPs) catalyzed this process. To assess TH involvement, Wistar rats were treated with α-methyl-L-tyrosine and tyrosol. Tyrosol was converted into hydroxytyrosol whilst α-methyl-L-tyrosine did not inhibit the biotransformation. The role of CYP was assessed in human liver microsomes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Furthermore, the liver cytochrome P450s, including CYP2D6 and CYP3A4, transformed tyrosol into hydroxytyrosol, which can contribute to therapeutic potential [ 58 ]. However, oleuropein was poorly or dose-dependently absorbed, and inhibited CYP3A [ 59 , 60 , 61 ]. Therefore, the tested olive BPseco downstream pathway in this study emphasizes their stability toward hydrolysis under simulated experimental conditions and TNDO mechanisms that are alike in olive milling processing and in the human gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the liver cytochrome P450s, including CYP2D6 and CYP3A4, transformed tyrosol into hydroxytyrosol, which can contribute to therapeutic potential [ 58 ]. However, oleuropein was poorly or dose-dependently absorbed, and inhibited CYP3A [ 59 , 60 , 61 ]. Therefore, the tested olive BPseco downstream pathway in this study emphasizes their stability toward hydrolysis under simulated experimental conditions and TNDO mechanisms that are alike in olive milling processing and in the human gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…The dietary phenol tyrosol, found in red wine, olives, and olive oil, is metabolized to hydroxytyrosol by CYP2A6, with minor contributions of CYP2D6 and CYP3A4 [ 186 ]. Both tyrosol and hydroxytyrosol have antioxidant effects; however, the metabolite, hydroxytyrosol, appears to exhibit greater antioxidant activity than tyrosol [ 187 ], suggesting that individuals with faster CYP2A6 enzyme activity and associated genotypes may benefit most from consumption of tyrosol-containing foods.…”
Section: Cyp2a6 and Dietary Substratesmentioning
confidence: 99%
“…Although there is a contribution of dopamine and tyrosine when alcohol is consumed in the formation of HT and TYR, this does not suffice to explain recoveries of HT and TYR [ 19 ]. We demonstrated in vivo, in animal models, and in vitro, in human liver biopsies, that the most likely explanation for higher recoveries of both phenolic compounds is the biotransformation of TYR to HT, a reaction regulated by the polymorphic enzymes CYP2D6 and CYP2A6 [ 20 ]. Ethanol contributes to this reaction by increasing TYR bioavailability and then favoring the biotransformation reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Further pre-clinical studies identified TYR as the metabolic precursor of HT [ 19 ]. TYR is endogenously bio transformed in humans into HT by means of the isoforms CYP2A6 and CYP2D6 [ 20 ]. HT endogenous generation after RW consumption could, in part, explain the beneficial effects derived from moderate wine consumption [ 17 ].…”
Section: Introductionmentioning
confidence: 99%